Morphology and adhesion on blood components in root surfaces treated by a piezoelectric ultrasonic: an in vitro study - Tsurumaki, Jackeline Nascimento [UNESP]; Souto, Bráulio Henrique Marques [UNESP]; Oliveira, Guilherme José Pimentel Lopes de [UNESP]; Sampaio, José Eduardo Cézar [UNESP]; Marcantonio, Rosemary Adriana Chierici [UNESP] (My University, 2013)
The aim of this study was to evaluate the morphology and adhesion of blood components on root surfaces instrumented with piezoelectric ultrasonic Piezon Master Surgery. Methods 10 teeth were used in this study. The teeth had their proximal divided into four areas that received different treatments: Group 1: untreated control Group 2: scaling with manual instrument; Group 3: scaling with ultrasound; Group 4: Scaling with manual instruments and ultrasound. We obtained 20 samples, 10 of which were used to analyze the morphology and the other 10 were used for analysis of adhesion of blood components. The specimens were analyzed by scanning electron microscopy. Photomicrographs were analyzed by the scores of adhesion of blood components and the index of root morphology. The results were statistically by the Kruskall-Wallis and Mann-Whitney with a significance level of 95%. Results The morphological analysis showed that the Group 1 had a surface unchanged in relation to other groups (Group 1 X Group 2 = 0.0025; Group 1 X Group 3 = 0.0003; Group 1 X Group 4 = 0.0003) and Group 2 presented a smoother surface compared to Group 1 and groups instrumented with ultrasound (Group 2 X Group 3 = 0.0025; Group 2 X Group 4 = 0.0025) there were no statistical differences between the Groups 3 and 4. analysis of adhesion of blood components showed that the Groups 2, 3 and 4 had no statistically significant differences between themselves, but more biocompatible surfaces promoted the surface untreated control (Group 1 X Group 2 = 0.02; Group 1 X Group 3 = 0.04; Group 1 X Group 4 = 0.005). Conclusion The instrumentation with piezoelectric ultrasonic promoted an irregular root surface, but did not negatively affect the adhesion of blood components.

Avaliar a morfologia e a adesão de células sanguíneas em superfícies radiculares instrumentadas com o ultrassom piezoelétrico Piezon Master Surgery. Métodos Foram utilizados nesse estudo 10 dentes que tiveram suas proximais divididas em 4 áreas que receberam diferentes tratamentos: Grupo 1: controle sem tratamento; Grupo 2: raspagem com instrumento manual; Grupo 3: raspagem com ultrassom; Grupo 4: associação instrumento manual e ultrassom. Foram obtidas 20 amostras, sendo que 10 foram utilizadas para análise da morfologia e as outras 10 foram utilizadas para a análise de adesão de elementos sanguíneos. Os espécimes foram analisados em microscópio eletrônico de varredura. As fotomicrografias foram analisadas através dos scores de adesão de elementos sanguíneos e pelo índice de morfologia radicular e os resultados foram analisados estatisticamente através dos testes de Kruskall-Wallis e de Mann-Whitney com nível de significância de 95%. Resultados A análise morfológica demonstrou que o Grupo 1 apresentou uma superfície inalterada em relação aos outros grupos (Grupo 1 X Grupo 2 = 0.0025; Grupo 1 X Grupo 3 = 0.0003; Grupo 1 X Grupo 4 = 0.0003), e o Grupo 2 apresentou uma superfície mais lisa em relação ao Grupo 1 e aos grupos instrumentados com ultrassom (Grupo 2 X Grupo 3 = 0.0025; Grupo 2 X Grupo 4 = 0.0025). Não houve diferenças estatísticas entre os Grupos 3 e Grupo 4. A análise de adesão de elementos sanguíneos demonstrou que o Grupo 2, Grupo 3 e Grupo 4 não apresentaram diferenças estatisticamente significantes entre si, porém promoveram superfícies mais biocompatíveis que a superfície controle sem tratamento (Grupo 1 X Grupo 2 = 0.02; Grupo 1 X Grupo 3 = 0.04;Grupo 1 X Grupo 4 = 0.005). Conclusão A instrumentação com ultrassom promoveu uma superfície radicular irregular, porém não afetou negativamente a adesão de elementos sanguíneos.
Análise da morfologia e da adesão de elementos sanguíneos em superfícies radiculares instrumentadas com ultrassom piezoelétrico: estudo in vitro
Keywords: Dental scaling; Regeneration; Ultrasonic; Raspagem dentária; Regeneração; Ultrassom